Management of intestinal obstruction in advanced malignancy. Issue 3 (September 2015) - Ferguson, Henry John Murray; Ferguson, Claire Irene; Speakman, John; Ismail, Tariq
Abstract Patients with incurable, advanced abdominal or pelvic malignancy often present to acute surgical departments with symptoms and signs of intestinal obstruction. It is rare for bowel strangulation to occur in these presentations, and spontaneous resolution often occurs, so the luxury of time should be afforded while decisions are made regarding surgery. Cross-sectional imaging is valuable in determining the underlying mechanism and pathology. The majority of these patients will not be suitable for an operation, and will be best managed in conjunction with a palliative medicine team. Surgeons require a good working knowledge of the mechanisms of action of anti-emetics, anti-secretories and analgesics to tailor early management to individual patients, while decisions regarding potential surgery are made. Deciding if and when to perform operative intervention in this group is complex, and fraught with both technical and emotional challenges. Surgery in this group is highly morbid, with no current evidence available concerning quality of life following surgery. The limited evidence concerning operative strategy suggests that resection and primary anastomosis results in improved survival, over bypass or stoma formation. Realistic prognostication and involvement of the patient, care-givers and the multidisciplinary team in treatment decisions is mandatory if optimum outcomes are to be achieved.